User Experience (UX) for Energy Awareness: A Global Bibliometric Analysis of Interface Design in Sustainability Contexts - Judijanto, Loso; Suda Nurjani, Ni Putu; Bunyamin, Ilham Akbar (Westscience Press, 2025)
As energy efficiency and environmental sustainability gain global importance, user-centered digital solutions have become vital in promoting energy awareness. This study presents a comprehensive bibliometric analysis of scholarly literature at the intersection of User Experience (UX), interface design, and sustainability, with a specific focus on how digital systems support behavioral change and energy literacy. Using the Scopus database and VOSviewer software, a total of 156 peer-reviewed articles published between 2000 and 2025 were analyzed to uncover co-occurrence patterns, author collaborations, keyword evolution, and country-level partnerships. The results identify sustainable development, user experience, and interface design as dominant research themes, while emerging trends such as artificial intelligence, visualization, and electronic commerce reflect a shift toward adaptive, intelligent systems for sustainability. The study reveals a strong research presence from China, the United States, and Europe, with notable gaps in Global South representation and education-oriented UX research. The findings offer critical insights into the thematic evolution and future directions of this interdisciplinary field, emphasizing the need for more inclusive, collaborative, and human-centered innovation in energy interface design.